Development of empirical fragility functions after the 2020 earthquakes in and around Türkiye - Açıkgöz, Nurullah. (Thesis (M.S.) - Bogazici University. Kandilli Observatory and Earthquake Research Institute, 2023., 2023)
In 2020, two major earthquakes occurred that caused life losses and severe damages to the built environment in Türkiye: On January 24 an earthquake of moment magnitude 6.8 in the East Anatolian Fault Zone nearby Elazı˘g (Sivrice) province and, an earthquake of moment magnitude 6.6 on the North Samos Fault in the Aegean Sea offshore Izmir (Seferihisar) province on October 30. Immediately following these devastating ground shakings, the Turkish Ministry of Environment, Urbanization and Climate Change conducted large-scale and detailed post-earthquake damage surveys in both regions. The observational damage data collected by the technical staff of the Ministry consisted of 92,800 structures in Elazı˘g and 213,776 structures in Izmir. This thesis aims to construct comprehensive empirical fragility functions from these two damage datasets by employing statistical methods. In order to examine the uncertainties, fragility curves are produced using different ground motion models and local soil information from different sources, and to consider these effects a ground motion model using a logic tree approach is proposed. Fragility curves for reinforced concrete moment-resisting frame type structures and unreinforced masonry structures, which are the predominant typologies in T¨urkiye, are proposed with their confidence intervals. Comparisons with the fragility functions for similar structures available in the literature are provided.
Keywords: Earthquakes -- Turkey.; East Anatolian Fault Zone (Turkey)